Challenges in the Enforcement of International Legal Framework Against Child Soldiering - Ekpa, Shedrack; Atidoga, Daniel Friday (UI Scholars Hub, 2025)
The war crime of child soldiering has contagiously blossomed, necessitating the application of several prohibitive legal standards for its extermination. As the impact of this heinous and atrocious crime soars, the multi-dimensional scope for the protection against child soldiering becomes more sternly entrenched. This article aims to interrogate this global and worrying phenomenon in the light of existing international legal framework. Alhough doctrinal in nature, this article relies on both primary and secondary sources of data. It was found that despite the high retinue of prohibitive norms as stipulated in various legal instruments, the war crime of child soldiering has continued to thrive with brazen impunity. It is recommended that more synergy be deployed towards ensuring effective co-operation amongst stakeholders with a view to enthroning purpose driven enforcement which has been identified as one of the innumerable challenges confronting the effectiveness of international law generally. Furthermore, State parties should fully align themselves with the provisions of applicable international instruments against child soldiering, based on the principle of pacta sunt servanda.